The Plant as Metaorganism and Research on Next-Generation Systemic Pesticides – Prospects and Challenges - Vryzas, Zisis (Frontiers in Microbiology, 2016)
Systemic pesticides (SP) are usually recommended for soil treatments and as seed coating agents and are taken up from the soil by involving various plant-mediated processes, physiological and morphological attributes of the root systems. Microscopic insights and next-generation sequencing combined with bioinformatics allow us now to identify new functions and interactions of plant-associated bacteria and perceive plants as meta-organisms. Host symbiotic, rhizo-epiphytic, endophytic microorganisms and their functions on plants have not been studied yet in accordance with uptake, tanslocation and action of pesticides. Root tips exudates mediated by rhizobacteria could modify the uptake of specific pesticides while bacterial ligands and enzymes can affect metabolism and fate of pesticide within plant. Over expression of specific proteins in cell membrane can also modify pesticide influx in roots. Moreover, proteins and other membrane compartments are usually involved in pesticide modes of action and resistance development. In this article it is discussed what is known of the physiological attributes including apoplastic, symplastic and trans-membane transport of systemic pesticides in accordance with the intercommunication dictated by plant-microbe, cell to cell and intracellular signaling. Prospects and challenges for uptake, translocation, storage, exudation, metabolism and action of systemic pesticides are given through the prism of new insights of plant microbiome. Interactions of soil applied pesticides with physiological processes, plant root exudates and plant microbiome are summarized to scrutinize challenges for the next-generation pesticides.